The Influence of Financial Inclusion, Financial Literacy and Digitalization on the Financial Performance of MSMEs in Pamekasan - Husnah, Fithiyatul; Susandini, Aprilina; Hadyarti, Vidi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Madura has extraordinary potential in developing a creative economy, one of which is Pamekasan Regency which has a dynamic entrepreneurial spirit. This is proven by the existence of 195,554 Micro, Small and Medium Enterprises (MSMEs). Even so, many MSMEs still experience obstacles in obtaining financial support. The complexity and perception that financial products are inaccessible often makes it difficult for them to find the services that best suit their business needs. This research aims to determine the influence of financial inclusion, financial literacy and digitalization on the financial performance of MSMEs in Pamekasan. The research focuses on MSME actors in Pamekasan Regency with a sample of 100 respondents using a quantitative approach, data collected through questionnaires and interviews, then analyzed using instrument tests, classical assumption tests, and multiple linear regression techniques. The research results show that financial inclusion, financial literacy and digitalization have a positive and significant influence on the financial performance of MSMEs in Pamekasan, both partially and simultaneously. So it is important to strengthen aspects of financial inclusion, financial literacy, and the application of digital technology in running business in Pamekasan Regency.